LSTM self-supervision for detailed behavior analysis - Brattoli, Biagio; Büchler, Uta; Ommer, Björn (2017 IEEE Conference on Computer Vision and Pattern Recognition (CVPR), 2017)
Behavior analysis provides a crucial non-invasive and easily accessible diagnostic tool for biomedical research. A detailed analysis of posture changes during skilled motor tasks can reveal distinct functional deficits and their restoration during recovery. Our specific scenario is based on a neuroscientific study of rodents recovering from a large sensorimotor cortex stroke and skilled forelimb grasping is being recorded.